The effect of ethical leadership and perceived organizational support on job satisfaction mediated by psychological empowerment - Rezha, Being; Dewi, I Gusti Ayu Manuati (International research journal of management, IT and social sciences, 2025)
Nurses are the largest representative of the health worker population in Indonesia, who play an important role in patient care, health, and safety. However, nursing is a field of work with a high level of stress and can trigger a decrease in job satisfaction. This also happened at Ari Canti Hospital in Gianyar Regency, Bali Province-Indonesia. The results of the Employee Satisfaction Survey in 2023 showed that 489 respondents had a job satisfaction level of 66.5%, and the nursing unit had the lowest satisfaction level among other units. This hospital has not met the level of employee job satisfaction that must be achieved, which is a minimum of 80% based on the requirements of the Hospital Accreditation Standards. This study aims to analyze the effect of ethical leadership and perceived organizational support on nurse job satisfaction with psychological empowerment as a mediating variable. Based on the Social Exchange Theory, the reciprocal relationship between nurses, superiors, and organizations plays an important role in creating job satisfaction. This study was conducted at Ari Canti Hospital with a sample of 154 nurses. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach.